A imagem discursiva do trabalho do educacional nos prescritos oficiais - Portela, Sonia Cristina (2006)
This work in Applied Linguistics inserts in the research line Language and Work and has as objective to identify the discourse image of the work of the professor in the official prescribed ones in order to understand its complexity. For in such a way, this research will be supported in the theoretical beddings of the Analysis of the discourse of French line praised by Dominique Maingueneau (1997/2002) and in the studies of Sciences of the Work, more specifically of the Ergonomics (René Amigues, 2002/2004) and of the Ergologia (Yves Schwartz, 1998/2000). Official ones are analyzed two prescribed, also called, in this research, of documents, which had been selected by presenting reference to the teacher´s work: (1) Educational Politics of the Secretariat of the Education of the State of São Paulo and (2) Rules for Elaboration of the Planning in the Schools and the Directions of Education, both of the year of 2004. These documents had been removed of the site htpp://cenp.edunet.sp.gov.br. The discourse analysis was made, first, in the studies of the interdiscourses relations for, after that, using itself of the linguistic categories of the marked forms of heterogeneidade and, finally, in the identification of the type of assignments the existence in documents. From the analysis, the character could be evidenced fluid of the lapsings, therefore they present themselves vacant however reveal normatizadoras in relation to teacher´s work. The presence of the enterprise discourse also is found in the prescribed ones, what it demonstrates the influence of this instance in the educational context. It could be perceived, also, that the prescribed ones for the teacher are not obtaining to day-by-day breach the barrier of the reality of its work in the e, consequently, perhaps, can there configure one of the possible causes for its anguish in the work